2023
DOI: 10.1029/2023jb027741
|View full text |Cite
|
Sign up to set email alerts
|

Glacial‐Interglacial Circulation and Climatic Changes in the South Indian Ocean (Kerguelen Plateau Region) Recorded by Detrital and Biogenic Magnetic Minerals

Yan Liu,
Catherine Kissel,
Alain Mazaud
et al.

Abstract: The Southern Ocean (SO) plays a fundamental role in global climate due to the presence of the intense eastward‐flowing Antarctic Circumpolar Current (ACC), one of the most important ocean current systems. The configuration of the frontal systems of the ACC is controlled by the orbital‐ and millennial‐scale variations of the Southern Hemisphere westerly winds (SHWW) and the SO upwelling. However, the reconstruction of paleoclimate and paleocurrent in the SO remains controversial possibly because of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…More recent studies primarily focused on the paleoclimatic implications of magnetofossils. For instance, many paleoenvironmental factors may possibly affect the abundance and diversity of magnetofossils such as primary productivity, aeolian influx, chemical weathering, and diagenesis (Y. Liu et al., 2023; Roberts et al., 2011; Wagner et al., 2021; Wang et al., 2023; Yamazaki, 2020; Zhang et al., 2021). Moreover, several studies have found that the magnetofossil abundance and morphological variations may reflect paleo‐oxygen levels (Chang et al., 2018, 2023; Rhoads et al., 1991; Xue et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies primarily focused on the paleoclimatic implications of magnetofossils. For instance, many paleoenvironmental factors may possibly affect the abundance and diversity of magnetofossils such as primary productivity, aeolian influx, chemical weathering, and diagenesis (Y. Liu et al., 2023; Roberts et al., 2011; Wagner et al., 2021; Wang et al., 2023; Yamazaki, 2020; Zhang et al., 2021). Moreover, several studies have found that the magnetofossil abundance and morphological variations may reflect paleo‐oxygen levels (Chang et al., 2018, 2023; Rhoads et al., 1991; Xue et al., 2022).…”
Section: Introductionmentioning
confidence: 99%